The voseo in Medellín as an expression of Antioquian identity - Ji Son Jang (Ikala: Revista de Lenguaje y Cultura, 2013)
It is claimed that through the time, the Colombian voseo could disappear from the country. However, in the city of Medellin, there has been a vital permanence of this way of treatment. In this article we want to show the way in which social attitudes surrounding the voseo in Medellin favor the continuation of this phenomenon, at least at this time. To carry out this research a questionnaire was applied to university students in Medellin, asking the questions that appeared regarding the voseo in Medellin and the social attitudes. Specifically, we asked them why the voseo was employed, and what they think about the members of their own community and the foreign members of this community using that way of speech. Informants state to use the voseo because it is part of their social identity regarding Medellin's group, as well as a way to show a strong sense of belonging to this group, showing positive points of view about this group and negative points of view on the persons not belonging to this group. For this reason, we can suppose that the voseo in Medellín will not disappear, at least in a short term.